Evidence-based surgery - McCulloch, P (2006)
Evidence-based medicine has attracted huge interest over the last eleven years in the UK. Various groups within the health care 'industry' have taken it up with great enthusiasm, often because they see in it a means of furthering a personal, political or factional agenda. It has been seized by health care purchasers and hospital management as a means of resisting pressure for expenditure, some groups of doctors in competition with others for patients or resources and enthusiasts for particular treatments. Conversely, there are many who have dismissed it as a fad, or a 'rebranding' of established principles of medical education and professional development, and who claim that they have been practising it all their working lives. Because of the number of different agendas for which it has proved a useful slogan, it is common to find doctors who are confused as to what evidence-based medicine is, or sceptical as to whether the phrase has real meaning. © 2006 Elsevier Ltd. All rights reserved.